Algumas notas acerca do Diteito internacional nas Constituições dos Estados Africanos Lusófonos - Loureiro Bastos, Fernando (2022)
The constitutional texts of the African Lusophone states (Angola, Cape Verde, Guinea-Bissau, Mozambique, and SAo Tomé and Principe) were influenced strongly by the Portuguese Constitution of 1976 with regard to the language used to draft them about International Law. The influence of the Portuguese constitution becomes particularly evident when compared with African constitutions affiliated to the francophone tradition or structured according to the common law legal system. In the constitutions of the Lusophone African states, with the exception of GuineaBissau, it is possible to find provisions specifically devoted to the incorporation of the sources of International Law into the juridical legal system of the States, with particular emphasis on the effects produced by treaties. With regard to the various stages of the conclusion of treaties, there is great concern about the constitutional organs which have internal competence to approve international commitments, in particular with reference to the matters that relate to the exclusive competence of the parliamentary bodies. In contrast to this, the initial state of negotiation and the signing of international commitments are not usually subject to significant regulation